Cross-Cultural Leadership Intelligence: Recommendations for Kenya - Service, Robert W; Loudon, David L; Kariuki, Kavore (Journal of Social Economics Research, 2014)
All leaders can improve their cultural intelligence (CQ) and every country can modify cultural norms toward advancing economically. CQ enables more effective cross-cultural leadership in the global economy. Based on analysis of the literature, experiences and survey results, our CQ recommendations start with self-assessment as key to successful cross-cultural interactions. In cross-cultural situations one must start by slowing down in order to develop more keen abilities to reflect on behaviors in order to generalize from what one discovers. Mental model development and flexibility, psychological hardness, curiosity, strategic thinking, and motivation all direct enhanced leadership across cultures. Aspiring cross-cultural leaders need guidelines for improvement. To meet these needs this paper builds on multiple-intelligence, leadership and crossing cultures research in order to propose useful global leadership models. The paper’s original contributions are: 1) guidelines for enhancing and selecting cross-cultural leaders; and, 2) “starting” point-example precepts for boosting economic development in Kenya.